2014
DOI: 10.1517/14656566.2015.981524
|View full text |Cite
|
Sign up to set email alerts
|

A review on the efficacy and safety of gabapentin in the treatment of chronic cough

Abstract: Gabapentin appears to be effective and well tolerated in the treatment of CC and in other sensory neuropathic disorders. Relevant clinical trials investigating its efficacy and safety profile in the treatment of cough are limited and further studies are needed. Gabapentin has been shown to cause minimal to no toxicity in overdose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
3

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 65 publications
1
17
1
3
Order By: Relevance
“…The magnitude of change in LCQ and cough severity in the pregabalin study was greater than the gabapentin study; however, adverse effects were higher. Pregabalin has greater abuse potential compared to gabapentin most likely due to its more rapid absorption and faster onset of action [103]. …”
Section: Resultsmentioning
confidence: 99%
“…The magnitude of change in LCQ and cough severity in the pregabalin study was greater than the gabapentin study; however, adverse effects were higher. Pregabalin has greater abuse potential compared to gabapentin most likely due to its more rapid absorption and faster onset of action [103]. …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to restore normal cough sensitivity and inhibit pathological cough under the premise of preserving the protective effect of cough re ex are an ideal therapeutic strategy. The rationale for gabapentin treating CRC is the similar central hypersensitivity of chronic cough to neuropathic pain and the proven e cacious effectiveness of gabapentin in chronic pain [22][23][24][25] . Our study has supported that gabapentin is an effective regimen for CRC, as indicated by a favorable response to gabapentin in the majority of recruited patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gabapentin: several case series and reports have described the use of gabapentin in chronic cough 48. A randomised controlled trial (n=62) found that gabapentin used for 10 weeks (up to a maximum dose of 1800 mg/day) resulted in a small improvement in LCQ score compared with placebo 49.…”
Section: Further Specialist Managementmentioning
confidence: 99%